2010
DOI: 10.1111/j.1468-5973.2010.00618.x
|View full text |Cite
|
Sign up to set email alerts
|

Team Coordination in Escalating Situations: An Empirical Study Using Mid‐Fidelity Simulation

Abstract: Abstract. The performance of teams, with different levels of domain-and crisis management experience, managing unexpected and escalating situations was observed by using a mid-fidelity ship-bridge simulation and analysed by applying the central concepts of joint activity coordination (Klein et al., 2005) as well as Woods' (2002) theory building on data overload. The coordination strategies used by the teams were evaluated by applying coordination process indicators and the concept of control. The paper discuss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 22 publications
(28 reference statements)
0
19
0
1
Order By: Relevance
“…communication, coordination), and the organization (e.g. safety culture) (Bergström, Dahlström, Henriqson & Dekker, 2010;Dekker & Lundström, 2007;McManus, Seville, Brunsdon, Vargo, 2007). In this paper an agenda for the development of conceptual fundaments of sharp end team training, and team performance assessment, will be outlined.…”
Section: Introductionmentioning
confidence: 99%
“…communication, coordination), and the organization (e.g. safety culture) (Bergström, Dahlström, Henriqson & Dekker, 2010;Dekker & Lundström, 2007;McManus, Seville, Brunsdon, Vargo, 2007). In this paper an agenda for the development of conceptual fundaments of sharp end team training, and team performance assessment, will be outlined.…”
Section: Introductionmentioning
confidence: 99%
“…Bergström et al (2010) have shown that a lack of structure and the absence of routines, in favor of an exaggerated belief in prestigeless collaboration, lead to uncertainty. It was confirmed by interviews that participants in certain exercises became passive because of overambitious, unstructured, and messy exercises (Powley and Nissen 2012).…”
Section: Discussionmentioning
confidence: 99%
“…It is operationalized as the result of different actors' ability to predict the behavior of each other, i.e., interpredictability, their common terminology, values and frameworks, i.e., common ground, their ways to exercise influence on each other, i.e., directability, together with their previous experiences, or assumptions, of working together, i.e., choreography (Klein et al 2004). It has been suggested that the macro cognitive framework is a promising one, and in further studies the language of control has been operationalized to map and follow the performance of a crisis management team, again based on their collective rather than individual performances (Bergström et al 2010, Palmqvist et al 2012). …”
Section: Models Of Joint Cognitive Activitymentioning
confidence: 99%
“…Interest in how the ability to adapt to unexpected and escalating situations varies with different levels of experience in both the domain of working and that of crisis management. Studies have been conducted focusing on how teams reached different levels of control based on how they coordinated their actions (Bergström et al 2010, Palmqvist et al 2012. The notion of coordination provides an analytic language locating the target of analysis at the functional level of the system studied.…”
Section: Models Of Joint Cognitive Activitymentioning
confidence: 99%